Anti-inflammatory Effect of a Novel Pectin Polysaccharide From Rubus chingii Hu on Colitis Mice - Kong, Yuanfang; Hu, Yulong; Li, Jieming; Cai, Juntao; Qiu, Yuanhao; Dong, Chunhong (Frontiers in Nutrition, 2022)
Rubus chingii Hu has been used as a functional food for a long time. A novel pectin polysaccharide named RCHP-S from R. chingii Hu was structurally identified and explored its anti-inflammatory effect on colitis mice. RCHP-S was composed of mannose, rhamnose, glucuronic acid, galacturonic acid, glucose, galactose, and arabinose. NMR spectroscopy and methylation analysis showed that RCHP-S was mainly composed of HG-type pectin domains but also contains a small amount of RG-I. The anti-inflammatory tests indicated that the mouse macrophage RAW 264.7 cells pretreated with RCHP-S could show a significant inhibitory effect on the mRNA level of iNOS, IL-1β, IL-6, and TNF-α in vitro. Polysaccharide RCHP-S reduced the enteritis symptoms in dextran sulfate sodium (DSS)-induced colitis mice by inhibiting released inflammatory factors. These results indicated that the R. chingii Hu polysaccharide can be used as food additives for the treatment of intestinal inflammation.